Analisis Tingkat Kerawanan Seismik Provinsi di Pulau Sumatera Menggunakan Parameter Gutenberg-Richter - Lola Amanda; Lailatul Husna Lubis; Ratni Sirait (Panthera : Jurnal Ilmiah Pendidikan Sains dan Terapan, 2026)
Sumatra Island has complex geological conditions as it is located in a collision zone between the northward-moving Indo-Australian Plate and the relatively stable Eurasian Plate. The interaction of these two plates forms two main tectonic structures: the subduction zone off the western coast of Sumatra and the Sumatra Fault Zone (SFZ). The latter exhibits varying seismic activity that has not yet been clearly mapped. This study aims to assess the level of seismic vulnerability across Sumatra Island by dividing the region into nine zones using the a-value and b-value parameters based on the Gutenberg-Richter relationship. Earthquake data from the USGS and IRIS catalogs for the period 1924-2024 were processed through a declustering procedure and subsequently analyzed using the Maximum Likelihood method with the assistance of ZMAP v6 software. The results show that the a-value across Sumatra ranges from 2.1 to 5.1, while the b-value ranges from 0.545 to 0.868. North Sumatra records the highest a- and b-values, at 3.82 and 0.786, respectively. In contrast, West Sumatra shows the lowest values, with an a-value of 2.9 and a b-value of 0.623. These findings not only reveal variations in seismic activity across Sumatra Island, but also provide a more detailed zonation of seismic hazard based on the Gutenberg-Richter parameters, which can serve as a basis for disaster mitigation planning and the development of earthquake-resistant infrastructure.